Quality of milled rice in different storage technologies. (27th March 2020) - Ara, Jeenat; Ali, Md. Rostom; Hossain, Mohammad Afzal; Awal, Md. Abdul; Alam, Md. Monjurul
Quality of milled rice deteriorates if it is not stored properly. Storage conditions alter the physicochemical properties of rice. The main objective of the study was to find out the sensual differences among different storage technologies and determine the consumer level of acceptance. Moisture content of stored milled rice was monitored during nine months of storage in different storage structures. The sensory quality of stored milled rice in three traditional storage technologies ( Kolshi, steel drum and plastic drum) and hermetic bag like GrainPro bag for two rice varieties ( Tulshimala and BRRI dhan49) was analysed for consumer's acceptability using panel test of 20 non-trained judges. The overall acceptance of cooked sample was determined based on the evaluation of the rice aroma, appearance, taste, and stickiness. Based on the taste, appearance, aroma and stickiness of cooked milled rice, GrainPro bag was found satisfactory in comparison to traditional storage technologies.